PENGARUH MODAL USAHA, VOLUME PRODUKSI, DAN VOLUME PENJUALAN TERHADAP LABA USAHA MIKRO BATIK TULIS PADA KAMPUNG BATIK TULIS GIRILOYO - Hikmi, Husaini Ismail; Firdarini, Khoirunnisa Cahya (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
The aim of this research is to empirically test the relationship between business capital, production volume and sales volume with the profit of the Giriloyo hand-written batik micro business. The type of research used in this research is quantitative research. The research subjects used were 35 Giriloyo hand-written batik micro-entrepreneurs with the data collection technique using a questionnaire. Data analysis techniques using classical assumption tests and multiple linear regression analysis. Data from the questionnaire was processed with the help of Microsoft Excel software and processed using the IBM SPSS STATISTICS 20 program. The results of this study show that business capital has no effect on the profits of hand-written batik micro businesses in the Giriloyo hand-written batik village. Production volume and sales volume influence the profits of hand-written batik micro businesses in Giriloyo hand-written batik village.